2019
DOI: 10.1038/s41598-019-43707-4
|View full text |Cite
|
Sign up to set email alerts
|

Glendonite occurrences in the Tremadocian of Baltica: first Early Palaeozoic evidence of massive ikaite precipitation at temperate latitudes

Abstract: The Tremadocian (Early Ordovician) is currently considered a time span of greenhouse conditions with tropical water surface temperature estimates, interpolated from oxygen isotopes, approaching 40 °C. In the mid-latitude Baltoscandian Basin, conodonts displaying low δ 18 O values, which suggest high temperatures (>40 °C) in the water column, are in contrast with the discovery of contemporaneous glendonite clusters, a pseudomorph of ikaite (CaCO 3 ·6H 2 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…A possible scenario could be that ikaite precipitation lowers the pH in the parent solution beyond the limit for metastable nucleation of ikaite and thereafter the mineral starts to transform and is replaced by calcite pseudomorphically. Calcite has been reported as the primary replacement mineral in naturally occurring pseudomorphs (glendonite) after ikaite 11,24,36,46 . Our experiments confirm this common observation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible scenario could be that ikaite precipitation lowers the pH in the parent solution beyond the limit for metastable nucleation of ikaite and thereafter the mineral starts to transform and is replaced by calcite pseudomorphically. Calcite has been reported as the primary replacement mineral in naturally occurring pseudomorphs (glendonite) after ikaite 11,24,36,46 . Our experiments confirm this common observation.…”
Section: Discussionmentioning
confidence: 99%
“…The results from these experiments may suggest that ikaite nucleation can also occur at temperature >7 °C in the natural environment. A recent study by Popov et al (2019) of fossil records in glendonite bearing strata suggested that ikaite nucleation probably occurred at water temperature >40 °C 36 . These findings call into question the use of ikaite as a paleotemperature indicator.…”
mentioning
confidence: 99%
“…There is a notable absence of glendonite occurrences for a prolonged period of time below the Carboniferous, spanning the Devonian, Silurian, and Middle-Upper Ordovician. Lower Ordovician glendonites have only recently been discovered and described (Popov et al, 2019;Mikhailova et al, 2019), as until recently, they were known as a kind of "anthraconite" and were not considered to be glendonites. Their findings are restricted to Baltoscandia.…”
Section: Glendonite Distribution In Space and Timementioning
confidence: 99%
“…There is a notable absence of glendonite occurrences for a prolonged period of time below the Carboniferous, spanning the Devonian, Silurian and Middle−Upper Ordovician. Lower Ordovician glendonites have only recently been discovered and described (Popov et al, 2019;Mikhailova et al, 2019), as until recently, they were known as a kind of 'anthraconite' and were not considered as glendonites. Their findings are restricted to Baltoscandia.…”
Section: Database Contentsmentioning
confidence: 99%